Trends and hotspots in environmental education research: Insights from a comparison of Indonesia and USA - Prayogo, Wisnu; Putra, Riansyah; Atika, Liana; Trimailuzi, Trimailuzi; Fitria, Laili; Fatahillah, Al; Estim, Abentin; Sarwa, Sarwa; Darwin, Darwin; Zubir, Moondra; Awfa, Dion; Siregar, Januar Parlaungan; Anggamulia, Muh. Ilham; Azizah, Rifka Noor (Education and Development Research, 2026)
Environmental education plays a critical role in shaping awareness, sustainable behavior, and civic responsibility. Despite the global growth of environmental education research, comparative analyses between countries with different socio-political and academic contexts remain limited. This study aims to examine the research landscape and thematic evolution of environmental education in Indonesia and the USA. A systematic bibliometric and thematic analysis was conducted on WoS publications from 1975–2025. The study integrates PRISMA-based systematic screening with bibliometric mapping using VOSviewer, enabling transparent article selection while revealing structural relationships among keywords, institutions, and research themes. A total of 812 articles were included after screening and eligibility assessment. The results reveal clear contrasts in research focus and collaboration structures. In the USA, dominant themes include pro-environmental behavior, science education, and urban green spaces, supported by dense institutional collaboration networks led by the University of Florida, Stanford, and Cornell. In contrast, Indonesian environmental education research emphasizes health, sanitation, education, and slum communities, with relatively limited inter-institutional collaboration. Keyword co-occurrence analysis indicates that while global clusters center on “environmental education” and “students,” Indonesian studies integrate context-specific topics such as “COVID-19,” “slums,” and “coastal communities.” This study contributes to environmental education knowledge mapping by providing a systematic cross-national bibliometric comparison that clarifies thematic priorities, collaboration patterns, and emerging research directions. The findings also support SDG-aligned research and policy development, particularly SDG 4.7 (education for sustainable development) and SDG 13 (climate action), by identifying opportunities to strengthen international collaboration and diversify thematic research agendas in environmental education.